“Where Does The Breath I Take From My Nose Go? Children’s Knowledge about Respiratory System - Berat Ahi; Sibel Balcı (Elementary Education Online, 2023)
Purpose of this research is to define the knowledge of children from different levels of schooling and age (5, 7 and 10 years old) about respiratory system, which is one of the biologically-based complex systems. Study was conducted in a mid-sized city in the northwest of Turkey. In the scope of the research, 20 children from each age group, thus a total of 60 children participated in the current study. Typical case sampling technique was used to form focus group. Data were gathered by using thinking aloud technique. It was concluded from the results of this research that children from focus group mostly underlined mouth, lungs and windpipe from respiratory system. By increasing age, the number of organs that children can name is increasing accordingly. In the age groups of five and seven, children named abdomen and stomach as a part of respiratory system, which was false. Also, it was detected that significant number of children from focus group do not have sufficient knowledge on how the respiratory system works. From the results of this research, it is clear that there is a need for different techniques and methods for teaching complex systems and for further research on complex systems with different techniques in order to determine prior knowledge on complex systems